THE RELATIONSHIP BETWEEN LEARNING HABITS, LEARNING ENVIRONMENT AT HOME AND NUMERICAL ABILITY WITH MATHEMATICS LEARNING OUTCOMES - Anis Ni'matus Sholihah; Aris Thobirin (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The results of students mathematics learning associated with many factors. Learning Habits, Learning Environment at Home and Numerical Ability are some of the factors that related to students mathematics learning outcomes. This research aims to determine the presence or absence of a positive and significant relationship between learning habits, learning environment at home and numerical ability with mathematics learning outcomes in students class VIII of even semester in SMP Muhammadiyah 2 Depok Sleman regency academic year 2016/2017. The population in this research was all students class VIII of even semester in SMP Muhammadiyah 2 Depok Sleman regency academic year 2016/2017. Samples were taken by random sampling technique to the classes derived class VIIIC as a class sample consisting of 32 students. The data collection techniques such as questionnaires techniques and test techniques. Data analysis used correlation analysis and multiple linear regression analysis. The results showed that there were positive and significant relationship between (1) learning habits with mathematics learning outcomes, with ; (2) learning environment at home with mathematics learning outcomes, with ; (3) Numerical Ability with mathematics learning outcomes, with ; (4) learning habits and learning environment at home with mathematics learning outcomes, with ; (5) learning habits and numerical ability with mathematics learning outcomes, with ; (6) learning environment at home and numerical ability with mathematics learning outcomes, with ; (7) learning habits, learning environment at home and numerical ability with mathematics learning outcomes, with multiple correlation coefficient  with linear regression equation  relatively large contribution  and  with double determination coefficient  and effective large contribution  and .